2007
DOI: 10.1159/000127386
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Gastric Cancer Patients with Bone Marrow Metastases

Abstract: Background: Gastric cancer with bone marrow metastases is known to pursue a rapidly deteriorating clinical course. We conducted a retrospective analysis to evaluate clinical manifestations and prognosis of gastric cancer patients with bone marrow metastases. Methods: Between September 1994 and February 2006, 39 gastric cancer patients with pathologically confirmed bone marrow dissemination were selected. Results: The majority of the patients showed younger age, poorly differentiated adenocarcinoma or signet ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
108
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 38 publications
5
108
0
2
Order By: Relevance
“…The prognosis of patients with solid cancers and bone marrow metastases was dismal in this study, in line with previous reports (Ringenberg et al, 1986;Wang et al, 1987;Ozkalemkas et al, 2005;Kim et al, 2007;Kwon et al, 2011). In addition to the use of antitumor treatment as identified in previous studies, our study identified 3 additional clinical factors predictive of survival in these patients groups: ECOG PS, primary tumor location, and platelet counts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The prognosis of patients with solid cancers and bone marrow metastases was dismal in this study, in line with previous reports (Ringenberg et al, 1986;Wang et al, 1987;Ozkalemkas et al, 2005;Kim et al, 2007;Kwon et al, 2011). In addition to the use of antitumor treatment as identified in previous studies, our study identified 3 additional clinical factors predictive of survival in these patients groups: ECOG PS, primary tumor location, and platelet counts.…”
Section: Discussionsupporting
confidence: 90%
“…Yu-Shin Hung 1 , Wen-Chi Chou 1 *, Tai-Di Chen 2 , Tse-Ching Chen 2 , Po-Nan Wang 1 , Hung Chang 1 , Hung-Chih Hsu 1 , Wen-Chi Shen 1 , Wei-Hong Cheng 3 , Jen-Shi Chen 1 * et al, 1992;Trillet-Lenoir et al, 1994;Kim et al, 2007;Kwon et al, 2011;Mehdi et al, 2011).…”
Section: Prognostic Factors In Adult Patients With Solid Cancers and mentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer cases with bone marrow involvement have very poor prognosis with a survival period ranging from 1.5 to 4 months [8,9]. Prognostic factors for poor survival are low performance status, multiple bone metastases, and elevated tumor markers.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastases in gastric cancer are rare and they usually appear late in the natural history of the disease; however, micrometastatic seeding in the bone may be evident in the early stage of the disease (5). Nevertheless, when these metastatic lesions occur, the prognosis is poor, as they can cause bone marrow suppression, anemia, cord compression and intravascular coagulation and can quickly lead to mortality (6). In early gastric cancer, a poorly differentiated carcinoma and the presence of signet-cells seem to be associated with bone metastases (7).…”
Section: Introductionmentioning
confidence: 99%